Pembuatan Papan Komposit dari Plastik Daur Ulang dan Serbuk Kayu serta Jerami Sebagai Filler - Mulana, Farid; Hisbullah, Hisbullah; Iskandar, Iskandar (Jurnal Rekayasa Kimia & Lingkungan, 2011)
Production of composites was done by mixing the filler and matrix. The common matrix used to produce composite is plastic ore with types of poly propylene, poly ethylene and others. To know the characteristics of composite boards made from recycled plastic type poly ethylene so this research was conducted. This research aims to create a composite board made of solid waste sawdust and straw as a filler and recycled plastics as the matrix and to find out more details of the influence of variable solid waste types and ratio of solid waste weight and plastic toward the quality of the composite board product. Composite board manufacturing process was carried out by hot press method at a temperature of 145 oC for 20 minutes. The composite board products are tested on value of hardness, tensile strength, and thermal value. The results showed that the use of sawdust as a filler resulted the composite hardness value that is better (R79,5) compared with straw (R67) at a ratio of filler composition: matrix of 80:20 respectively. The use of sawdust also gives the value of tensile strength of 6.86 MPa that is better than the using a straw that valued of 3.62 MPa at composition ratio of filler: to matrix (60:40). Largest amount of heat needed to melt the composite boards are 31.19 J/g and 14.02 J/g at composition ratio sawdust: recycled plastics of 80:20 and at composition ratio straw: recycled plastics of 80:20, respectively. Visually composite board with a composition of sawdust:plastic HDPE 50:50 looks better with bright colors and shiny.Keywords: Composite, Solid waste, Plastic, Matrix, Filler, Poly ethylene